Frameworks and Models for Disseminating Curated Research Outcomes to the Public. (April 2019) - Clifton-Ross, Jaime; Dale, Ann; Newell, Robert
In our post-truth society, mobilizing "facts" and "evidence" has never been more important. We live in an age that is paradoxically information rich due to the proliferation of Internet Communication Technologies (ICTs) and information poor due to the spread of misinformation. Academic research outcomes are traditionally disseminated via peer-reviewed publications, conference presentations, and in the classroom; however, this research is not often effectively communicated to both decision makers and the general public(s). There is no perfect way of disseminating research outcomes; however, there are lessons to be learned from curatorial and communication frameworks developed in museums as these institutions have a long history educating and engaging the public. This article explores the new concept of "research curation, " or rather the enhanced dissemination of curated research outcomes to reach diverse audiences. Closing the "gap" between academia and the public is essential for increasing civic literacy around issues that threaten sustainability. By adapting curatorial and communication methods developed in museums along with ICT models, the practice of "research curation" can be an effective framework for improved dissemination of academic knowledge.